(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In fact, there is no need to introduce Karimboy Kurambaev. He is well known. Literary critics recognize the teacher as the most active critic, as well as a mature supporter of the literary relations of the three peoples (Uzbek, Karakalpak, Turkmen). His scientific researches and textbooks are not only a support for university students, but also in the textbooks of Turkmen classes of secondary schools of the Republic of Karakalpakstan.Some demand that they show special respect to the lesser by showing their older age. The teacher, on the other hand, insists that others do not notice that we have condemned the eighties. Anyone who doesn’t know them by their appearance will give them 60-65 years. Still, he is embarrassed that he took it out to the old man. 80 years is not a small date anyway. Because before reaching this age, a person goes through all the hardships of life and goes through many trials of life ...Before we talk about the Master, we feel in our hearts how interesting it is to express our heartfelt respect and sincerity to the teachers who, when the opportunity arises, give light and enlightenment to others, who are a great spiritual helper. The words, teachings and advice of such people, who have seen the cop and called the school of life, are exemplary in their wise actions. Those who follow them and follow their example will never go astray. There is an instructive wisdom in our people that a disciple who does not have a teacher will be promoted to any position. Indeed, the role of the teacher is important in the formation of each person as a truly competent person. Therefore, talking about the teacher, showing respect is both a duty and an obligation for every student.